PERAN MEDIASI PENGUNGKAPAN LINGKUNGAN PADA PENGARUH AKUNTANSI LINGKUNGAN DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN - FEBRIANTO WAILANDUW, SATRIO (Jurnal Akuntansi AKUNESA, 2017)
This study aimed to examine the influence of environmental accounting and environmental performance to the company’s value, in addition this study also tests the disclosure of the environment as a mediation variable. Using quantitative research method and Structural Equation Modeling (SEM) analysis, this study finds that environmental accounting and environmental performance have an effect on company’s value, but environmental disclosure can not mediate the relationship between environmental accounting and environmental performance to firm value.   Keywords: Environmental Accounting, Environmental Performance, Company    Value, Environmental Disclosure.